2021
DOI: 10.1080/01612840.2021.1929595
|View full text |Cite
|
Sign up to set email alerts
|

‘Working as a Real Nurse’: Nursing Students’ Experiences of a Clinical Education Ward in Psychiatric Care

Abstract: Although the concept of clinical education wards has shown encouraging outcomes regarding nursing students' satisfaction with clinical placements in somatic care, the existing research in a psychiatric context is sparse. This study aims to explore nursing students' experience during clinical education at a psychiatric clinical education ward. A qualitive descriptive study with content analysis, using interviews with 16 bachelor's degree nursing students was conducted. The results indicated that an enriched and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“… Melrose and Shapiro (1999) noted that students who did not feel included by staff during their clinical rotation eventually stopped being involved in staff groups, seeking out alternatives to use their time well. Alternatively, Vuckovic et al (2021) indicated that students viewed the mental health clinical placement as positive, in part, when they have an enriched learning environment where student preceptors and staff are available to meet the students’ academic needs and provide emotional support. Students’ connections and time with their preceptor or clinical instructor can profoundly influence their experience during mental health clinicals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Melrose and Shapiro (1999) noted that students who did not feel included by staff during their clinical rotation eventually stopped being involved in staff groups, seeking out alternatives to use their time well. Alternatively, Vuckovic et al (2021) indicated that students viewed the mental health clinical placement as positive, in part, when they have an enriched learning environment where student preceptors and staff are available to meet the students’ academic needs and provide emotional support. Students’ connections and time with their preceptor or clinical instructor can profoundly influence their experience during mental health clinicals.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to simulation, at the end of a clinical day, the students should be given time to debrief with clinical faculty to discuss the occurrences of the day. Vuckovic et al (2021) reported students discussed the importance of relating theoretical concepts to the individual patients in their care to develop concepts learned in the didactic lecture. In addition, checking in with students’ emotional states throughout the day and during the debriefing period is essential ( Melrose & Shapiro, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This support can be guided by a reflective approach to support nursing students in taking responsibility in the care for the patient and in preparing for their future professional role as a carer. Moreover, the importance of a supportive clinical learning environment provided by staff, supervisors and peer learning has been emphasized (Vuckovic et al, 2021 ). This is in line withCant et al ( 2021 ) who described that the educational atmosphere is associated with the supervisory relationship, the leadership of the ward and the premises where nursing takes place rather than the performance of clinical nursing tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of nursing students' recovery attitudes and education in psychiatry are sparse ( 17 ). However, in Australia, challenges with implementing personal and social recovery in recovery‐focused services have been ascertained ( 18 ).…”
Section: Introductionmentioning
confidence: 99%